Loss of Ezh2 in the medial ganglionic eminence alters interneuron fate, cell morphology and gene expression profiles - Rhodes, Christopher T.; Asokumar, Dhanya; Sohn, Mira; Naskar, Shovan; Elisha, Lielle; Stevenson, Parker; Lee, Dongjin R.; Zhang, Yajun; Rocha, Pedro P.; Dale, Ryan K.; Lee, Soohyun; Petros, Timothy J. (Frontiers in Cellular Neuroscience, 2024)
Enhancer of zeste homolog 2 (Ezh2) is responsible for trimethylation of histone 3 at lysine 27 (H3K27me3), resulting in repression of gene expression. Here, we explore the role of Ezh2 in forebrain GABAergic interneuron development. Loss of Ezh2 increases somatostatin-expressing (SST+) and decreases parvalbumin-expressing (PV+) interneurons in the forebrain. We observe fewer MGE-derived interneurons in the first postnatal week, indicating reduced interneuron production. Intrinsic electrophysiological properties in SST+ and PV+ interneurons are normal, but PV+ interneurons display increased axonal complexity in Ezh2 mutant mice. Single nuclei multiome analysis revealed differential gene expression patterns in the embryonic MGE that are predictive of these cell fate changes. Lastly, CUT&Tag analysis revealed that some genomic loci are particularly resistant or susceptible to shifts in H3K27me3 levels in the absence of Ezh2, indicating differential selectivity to epigenetic perturbation. Thus, loss of Ezh2 in the MGE alters interneuron fate, morphology, and gene expression and regulation.